APOL1 risk variants affect podocyte lipid homeostasis and energy production in focal segmental glomerulosclerosis. Issue 3 (30th January 2021) - Ge, Mengyuan; Molina, Judith; Ducasa, G Michelle; Mallela, Shamroop K; Varona Santos, Javier; Mitrofanova, Alla; Kim, Jin-Ju; Liu, Xiaochen; Sloan, Alexis; Mendez, Armando J; Banerjee, Santanu; Liu, Shaoyi; et al.
Abstract: Lipotoxicity was recently reported in several forms of kidney disease, including focal segmental glomerulosclerosis (FSGS). Susceptibility to FSGS in African Americans is associated with the presence of genetic variants of the Apolipoprotein L1 gene (APOL1) named G1 and G2. If and how endogenous APOL1 may alter mitochondrial function by the modifying cellular lipid metabolism is unknown. Using transgenic mice expressing the APOL1 variants (G0, G1 or G2) under endogenous promoter, we show that APOL1 risk variant expression in transgenic mice does not impair kidney function at baseline. However, APOL1 G1 expression worsens proteinuria and kidney function in mice characterized by the podocyte inducible expression of nuclear factor of activated T-cells (NFAT), which we have found to cause FSGS. APOL1 G1 expression in this FSGS-model also results in increased triglyceride and cholesterol ester contents in kidney cortices, where lipid accumulation correlated with loss of renal function. In vitro, we show that the expression of endogenous APOL1 G1/G2 in human urinary podocytes is associated with increased cellular triglyceride content and is accompanied by mitochondrial dysfunction in the presence of compensatory oxidative phosphorylation (OXPHOS) complexes elevation. Our findings indicate that APOL1 risk variant expression increases the susceptibility to lipid-dependent podocyte injury, ultimately leading to mitochondrial dysfunction.